2003
DOI: 10.1086/345523
|View full text |Cite
|
Sign up to set email alerts
|

SDSS J094857.3+002225: A Very Radio Loud, Narrow‐Line Quasar with Relativistic Jets?

Abstract: We report the identification of a very radio loud, narrow-line quasar, SDSS J094857.3+002225, discovered in the Sloan Digital Sky Survey (SDSS) early data release (EDR). With FWHM ðH Þ % 1500 km s À1 and undetected [O iii] 4959, 5007 SDSS J094857.3+002225 is consistent with the conventional definition of narrow-line Seyfert 1 galaxies (NLS1s). Its strong optical Fe ii emission [R 4570 f ðFe ii 4570Þ= f ðH Þ % 1:59] is also typical of NLS1s. With a radio loudness RL ð f ;4:85 GHz =f ;B Þe1000 and radio power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
163
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(182 citation statements)
references
References 30 publications
19
163
0
Order By: Relevance
“…Thus, the first discoveries of RLNLS1s (e.g. Remillard et al 1986, Oshlack et al 2001, Zhou et al 2003 seemed to be exceptions, rather than the tip of an iceberg. The early surveys revealed only a handful of objects: 11 by Zhou & Wang (2002) and Komossa et al (2006a), and 16 by Whalen et al (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the first discoveries of RLNLS1s (e.g. Remillard et al 1986, Oshlack et al 2001, Zhou et al 2003 seemed to be exceptions, rather than the tip of an iceberg. The early surveys revealed only a handful of objects: 11 by Zhou & Wang (2002) and Komossa et al (2006a), and 16 by Whalen et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…with the ratio between radio and optical flux densities greater than 10. One source is also in the present sample (J0948 + 0022, Zhou et al 2003), while we have discarded the other (J1722 + 5654, Komossa et al 2006b) because of its steep radio index (see Sect. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The optical spectrum of PMN J0948+0022 exhibits the usual characteristics of NLS1s (cf. Osterbrock & Pogge 1985;Goodrich 1989): FWHM(Hβ) = 1500 ± 55 km s −1 , [OIII]/Hβ < 3, strong optical FeII emission (Zhou et al 2003). Such types of AGN are generally radio quiet (Ulvestadt et al 1995;Komossa et al 2006), so it was a surprise to detect strong radio emission.…”
mentioning
confidence: 99%
“…Zhou et al (2003) first reported the unexpected connection of its NLS1 character with strong and flat-spectrum radio emission. The optical spectrum of PMN J0948+0022 exhibits the usual characteristics of NLS1s (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation